Female EFL Preservice Teachers Speech Acts Used in Classroom Interaction - Isli Iriani Indiah Pane; Arbain Arbain (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: Using speech acts in the learning process by teachers and preservice teachers is inevitable. However, there are still many preservice EFL teachers who need help to use these speech acts effectively. This study aims to determine the use of directive speech acts and the reasoning by three Female EFL Preservice Teachers (FEPT). Methodology: This research was conducted on three female students participating in the Practical Field Experience II program at three Samarinda Vocational High Schools. To collect data, the researcher observed three FEPT people carrying out the teaching and learning process by recording videos. Then, to get reasons for using the speech acts, the researcher conducted interviews with them. Findings: This study found six types of speech acts: asking, requesting, advising, begging, commanding, and forbidding. The most used speech is asking. Then, the reason for using these speech acts is to make students more active and able to follow the lesson well in class. Conclusion: This study concluded the importance of mastering pragmatic competence by FEPT before teaching and learning. By mastering these competencies, FEPT could effectively carry out the teaching and learning process. Originality: This finding complements a large amount of previous literature on the use of directive speech acts by teachers and EFL preservice teachers. By examining the use of directive speech acts by female EFL preservice teachers, the researcher hopes to complement the lack of research on this topic.